Allogeneic mesenchymal stromal cell therapy in kidney transplantation: should repeated human leukocyte antigen mismatches be avoided? - Bezstarosti, Suzanne; Erpicum, Pauline; Maggipinto, Gianni; Dreyer, Geertje J.; Reinders, Marlies E. J.; Meziyerh, Soufian; Roelen, Dave L.; De Fijter, Johan W.; Kers, Jesper; Weekers, Laurent; Beguin, Yves; Jouret, François; et al. (Frontiers in Genetics, 2024)
Mesenchymal stromal cells (MSCs) have immunomodulatory properties and are therefore considered promising tools in kidney transplantation. Although most studies have been conducted with autologous MSCs, using allogeneic MSCs as an off-the-shelf product is more feasible in clinical settings. However, allogeneic MSCs could potentially induce an immune response, which might eventually be directed towards the kidney allograft because of shared human leukocyte antigen (HLA) epitope mismatches between the kidney and MSC donor. In this study, we performed in-depth analyses of two cohorts (n = 20) that received third-party MSC therapy after kidney transplantation. While the Neptune Study from Leiden University Medical Center specifically selected MSC to avoid repeated HLA antigen mismatches between kidney and MSC donors, the study from the University of Liège did not perform specific MSC selection. The comparative analyses of amino acid mismatches between these cohorts showed that MSC selection to avoid repeated HLA mismatches at the split antigen level was not sufficient to prevent repeated mismatches at the amino acid level. However, repeated amino acid mismatches were not associated with the occurrence of donor-specific antibodies (DSAs). Thus, the clinical relevance of repeated amino acid mismatches seems to be limited with regard to the risk of DSA formation. Since DSA formation was limited (3 of 20 patients) in this study, larger studies are required to investigate the relevance of preventing repeated HLA mismatches in allogeneic MSC therapy in kidney transplantation.